The effect of MgO nano-particles on Bi-2223 high temperature superconductors prepared by chemical sol-gel method - M. Eshraghi; P. Kameli; H. Salamati; E. Abdolhosseini Sarsari (Iranian Journal of Physics Research, 2008)
In this paper, two La0/8sr0/2mno3 samples, isotropic (press without magnetic field) and anisotropic (press with magnetic field) have been prepared. Then we have investigated structural, magnetic and magnetotransport properties of these samples using XRD, SEM, Ac susceptibility and magnetoresistance measurements. These studies show that a magnetic property of anisotropic sample is improved and magnetoresistance is decreased.